Exploring the relationship between circular tourism and tourist satisfaction: Empirical evidence - Minh, Dinh Hoang; Huong, Hoang Thi; Thang, Do Van; Hoang, Tran Vinh; Cuong, Tran (Journal of Tourism Management Research, 2025)
This study examines the impact of circular tourism on tourist satisfaction at travel destinations, emphasizing its role in promoting sustainability and enhancing visitor experiences. A survey was conducted with 314 tourists at a selected destination using a random sampling method. The collected data were analyzed using SPSS 26.0 and AMOS 20 to test the relationships among circular tourism, destination image, sustainable tourism, and tourist satisfaction. The results indicate that circular tourism positively influences destination image, sustainable tourism, and tourist satisfaction. Additionally, destination image enhances both sustainable tourism and tourist satisfaction, while sustainable tourism also contributes positively to satisfaction. Furthermore, demographic factors are found to impact these variables, highlighting their role in shaping tourism experiences. Circular tourism plays a crucial role in improving destination image, promoting sustainable tourism practices, and increasing tourist satisfaction. These insights provide valuable guidance for tourism stakeholders in developing sustainable tourism strategies.